2
$\begingroup$

Show that for $X \in \mathrm{M}_n(\mathbb{C})$ and any orthonormal basis $\{u_1, \ldots , u_n\}$ of $\mathbb{C}^n$, we have $$\|X\|^2=\sum_{j,k}^n|\langle u_j,Xu_k\rangle |^2.$$

My Attempt:

I thought this to prove using projection formula as

to find coordinate of $X_{ij}=\langle u_i,Xu_j\rangle$.

But I was thinking I am missing something. As this is $10$ mark question with just one line argument How it was ?

Please give me hint .I wanted to solve this problem

Any Help will be appreciated

$\endgroup$
  • $\begingroup$ How do you define $\lVert X\rVert$? $\endgroup$ – José Carlos Santos Feb 10 at 16:46
  • $\begingroup$ $||X||$=$\sum|X_{ij}|^2$ Sir this is Hilbert Smidt norm $\endgroup$ – MathLover Feb 10 at 16:48
2
$\begingroup$

Define a unitary map by $Ue_k = u_k$ for every $k=1,2,\ldots,n$, where $\{e_1,e_2,\ldots, e_n\}$ is the standard basis of $\Bbb C^n$. Then, we have $$\begin{align*} \sum_{j=1}^n\sum_{k=1}^n\left|\langle u_j,Xu_k\rangle\right|^2&=\sum_{j=1}^n\sum_{k=1}^n\left|\langle Ue_j,XUe_k\rangle\right|^2\\&=\sum_{j=1}^n\sum_{k=1}^n\left|\langle e_j,U^*XUe_k\rangle\right|^2\\&=\|U^*XU\|^2\\&=\text{tr}(U^*X^*UU^*XU)\\&=\text{tr}(U^*X^*XU)\\&=\text{tr}(X^*XUU^*)\\&=\text{tr}(X^*X)=\|X\|^2. \end{align*}$$

As a different approach, we can use Parseval's identity $$\begin{align*} \sum_{k=1}^n\sum_{j=1}^n\left|\langle u_j,Xu_k\rangle\right|^2 &=\sum_{k=1}^n\|Xu_k\|^2\\&=\sum_{k=1}^n\sum_{j=1}^n\left|\langle e_j,Xu_k\rangle\right|^2 \\&=\sum_{j=1}^n\sum_{k=1}^n\left|\langle X^*e_j,u_k\rangle\right|^2 \\&=\sum_{j=1}^n\sum_{k=1}^n\|X^*e_j\|^2 \\&=\sum_{j=1}^n\sum_{k=1}^n\left|\langle X^*e_j,e_k\rangle\right|^2 \\&=\sum_{j=1}^n\sum_{k=1}^n\left|\langle e_j,Xe_k\rangle\right|^2 \\&=\sum_{j=1}^n\sum_{k=1}^n\left|X_{jk}\right|^2 =\|X\|^2. \end{align*}$$

$\endgroup$
0
$\begingroup$

In this answer we look at a vector of $n$ coordinates as a column matrix. That is, a matrix with $n$ rows and $1$ column. First note that identity $$ \left\|X\right\|^2=\sum_{j=1}^n\sum_{k=1}^n|\langle u_j,Xu_k\rangle |^2\qquad (\ast) $$ is valid when the basis $\{u_1,\ldots,u_n\}$ of $\mathbb{C}^n$ is the canonical basis $\{e_1,\ldots,e_n\}$ of $\mathbb{C}^n$. Let any orthonormal basis $\{u_1,\ldots,u_n\}$ of $\mathbb{C}^n$. Let $U$ be the matrix whose columns are $u_1,\ldots, u_n$. That is, $$ U=\left[\; u_1 | \ldots |u_j|\ldots |u_n\;\right] $$ Note that $$ X\cdot U= X\cdot \left[\; u_1 | \ldots |u_j|\ldots |u_n\;\right]= \left[\; X\cdot u_1 | \ldots |X\cdot u_\ell|\ldots |X\cdot u_n\;\right] $$ and $$ U^\ast X\cdot U= U^\ast\left[\; X\cdot u_1 | \ldots |X\cdot u_j|\ldots |X\cdot u_n\;\right]= \big[\langle u_i, Xu_j \rangle \big]_{n\times n} $$ Then $$ \left\| U^\ast X U \right\|^2 = \left\| \big[\langle u_i, Xu_j \rangle \big]_{n\times n} \right\|^2 = \sum_{i=1}^{n}\sum_{j=1}^{n} |\langle u_i, Xu_j \rangle| ^2 $$ If $U=(U_{ij})_{n\times n}$ and $U^\ast=(U^\ast_{ij})_{n\times n}$ then $UU^\ast=(U_{ij})_{n\times n}\cdot(U_{ij})_{n\times n}=(\sum_{k=1}^{n}U_{ik}U^\ast_{kj})_{n\times n}=I_{n\times n}$. More explicitly, $$ \sum_{k=1}^{n}U_{ik}U^\ast_{kj}=\begin{cases} 1 & \mbox{if } i=j\\ 0 & \mbox{if } i\neq j\end{cases} $$ Now we have \begin{align} \left\|U^\ast \cdot X \cdot U\right\|^2 =& \left\| (U^\ast_{ij})_{n\times n}\cdot (X_{k\ell})_{n\times n}\cdot (U_{pq})_{n\times n} \right\|^2 \\ =& \left\| (\sum_{\alpha=1}^nU^\ast_{i\alpha}\cdot X_{\alpha\ell})_{n\times n}\cdot (U_{pq})_{n\times n} \right\|^2 \\ =& \left\| (\sum_{\beta=1}^{n}\sum_{\alpha=1}^nU^\ast_{i\alpha}\cdot X_{\alpha\beta}\cdot U_{\beta q})_{n\times n} \right\|^2 \\ =& \sum_{i=1}^{n}\sum_{q=1}^{n} \sum_{\beta=1}^{n}\sum_{\alpha=1}^n U^\ast_{i\alpha}\cdot X_{\alpha\beta}\cdot U_{\beta q} \cdot \overline{U^\ast_{i\alpha}\cdot X_{\alpha\beta}\cdot U_{\beta q}} \\ =& \sum_{\beta=1}^{n}\sum_{\alpha=1}^n X_{\alpha\beta}\cdot \overline{X_{\alpha\beta}} \sum_{i=1}^{n}\sum_{q=1}^{n} U_{\beta q} \cdot U^\ast_{i\alpha}\overline{U_{\beta q} \cdot U^\ast_{i\alpha}} \\ =& \sum_{\beta=1}^{n}\sum_{\alpha=1}^n X_{\alpha\beta}\cdot \overline{X_{\alpha\beta}} \Big( \sum_{i=q}^{n} U_{\beta q} \cdot U^\ast_{i\alpha}\overline{U_{\beta q} \cdot U^\ast_{i\alpha}} + \sum_{1\leq q<i\leq n}^{n} U_{\beta q} \cdot U^\ast_{i\alpha}\overline{U_{\beta q} \cdot U^\ast_{i\alpha}} \\ &\hspace{9cm}+ \sum_{1\leq i<q\leq n}^{n} U_{\beta q} \cdot U^\ast_{i\alpha}\overline{U_{\beta q} \cdot U^\ast_{i\alpha}} \Big) \\ =& \sum_{\beta=1}^{n}\sum_{\alpha=1}^n X_{\alpha\beta}\cdot \overline{X_{\alpha\beta}} \Big( 1 + 0 + 0 \Big) \\ =& \sum_{\beta=1}^{n}\sum_{\alpha=1}^n X_{\alpha\beta}\overline{X_{\alpha\beta}} \\ =& \left\|X\right\|^2 \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.